Sp1 Plays an Important Role in Vascular Calcification Both In Vivo and In Vitro. Issue 6 (23rd March 2018) - Zhang, Xinyu; Li, Rui; Qin, Xiaoteng; Wang, Lei; Xiao, Jie; Song, Yu; Sheng, Xi; Guo, Mengqi; Ji, Xiaoping
Abstract : Background: Vascular calcification and increased cardiovascular morbidity and mortality are closely related in patients with end‐stage renal disease and diabetes mellitus. Specific protein 1 (Sp1) is a transactivation molecule that plays a crucial role in the regulation of apoptosis, fibrosis, angiogenesis, and other pathological disorders. There is evidence that specific protein 1 (Sp1) directly stimulates the transcription of bone morphogenetic protein 2 (BMP2) and that BMP2 plays a key role in the calcification process in the BMP2–expressing F9 cell model system. Here, we investigated whether Sp1 plays an important role in vascular calcification and its potential regulatory mechanism in vascular calcification. Methods and Results: In this study, vascular calcification was induced in male Wistar rats by administration of nicotine (25 mg/kg) and vitamin D3 (300 000 IU/kg). These rats were randomly selected for treatment with adenovirus harboring Sp1 knockdown gene or empty virus. The mechanism of Sp1 in vascular smooth muscle cells cultured in high phosphate medium was studied. Based on our findings, the Sp1 gene silencing or inhibition improved calcium deposition, which was partly achieved by inhibiting phenotype switch, apoptosis, and matrix vesicle release of vascular smooth muscle cells. Moreover, Sp1 can activate BMP2 transcription by binding to the Sp1‐binding element of the BMP2 promoter. Conclusions: Overall, elevated Sp1 exerts a pro‐apoptotic effect, promoting BMP2 transcription and further accumulating vascular calcification. Proper and timely regulation of Sp1 expression may be a potential strategy for treatment of aging, end‐stage renal disease, and diabetic‐related macrovascular disease treatment.